Comparación entre la respuesta de la actividad muscular lumbar en plataforma vibratoria y en ejercicio clásico de squat isométrico en 30º y 60º. (A comparison of the lumbar muscle activity responsein 30º and 60º isometric squat between whole-body vibration and a classic exercise). - Alejandro Santos-Lozano; Fernanda Santin-Medeiros; Pedro J. Marín; Sonsoles Hernández-Sánchez (Ramón Cantó Alcaraz, 2012)
Whole-body vibration (WBV) has improved as a variety of exercises, so it is necessary know muscles responses to the vibration stimulus.The aim of this work was to study and to compare the change in muscle activation in the lumbar area and lower body between the whole-body vibration exercise and classic strength exercises in isometric squat.23 subjects were exposed to six different loads in one of each exercise mode: vibration or classic strength. Both exercises were performed at 30º and 60º semi-squat position. Muscle activity of the lower body and lumbar area was measured using surface electromyography activity (EMG).The results showed that the response of lumbar area in WBV was lower than in the classic strength exercise at the same value of lower body sEMG. Lumbar sEMG was highest for the classic exercise. Moreover, during 30º squat sEMG was higher than during 60ºsquat. Resumen El aumento del uso de la plataforma vibratoria como forma de realizar ejercicio conlleva la necesidad de conocer las respuestas musculares al estímulo de la misma.El objetivo de este trabajo ha sido estudiar y comparar la respuesta de la activación muscular de la zona lumbar y del tren inferior en el trabajo de plataforma vibratoria con el trabajo clásico de fuerza en un squat isométrico.23 sujetos fueron sometidos a 6 condiciones de vibración y a 6 de un trabajo clásico de pesas. Se analizó la sEMG del tren inferior y de la zona lumbar en un trabajo isométrico de un squat con flexión de 30º y 60º de rodilla.Los resultados muestran que para un mismo valor de sEMG del tren inferior, los valores de sEMG de la zona lumbar son menores en el ejercicio vibratorio. Existiendo en el trabajo de pesas una mayor exigencia en la zona lumbar. Además, con una flexión de 30º la activación muscular es mayor en todas las condiciones. (p<0,05)